THE MODERNIZATION OF SOCIETY AND TRANSFER OF POWER IN MUSLIM COUNTRIES - YOVKOCHEV, Shukhrat (CENTRAL ASIA AND THE CAUCASUS, 2009)
Power and its transfer is a key issue in Islam and is related to the traditional and basic values of national and religious identity, as well as to reform and democracy in contemporary Muslim societies. The transfer to new democratic methods and forms of rule in traditional societies, as most Muslim countries still are, is usually a slow and arduous process. In such societies, the people’s traditional mindset and mentality, particularly among those who lead a settled way of life, transform at a slower pace than in Western countries. But there is no doubt that in the globalizing world this process is gaining momentum and becoming an irreversible political phenomenon. At present, several new trends are emerging that determine the degree to which the region is being drawn into globalization. But, regardless of the level of these transformation processes, the influence of the spiritual component, which largely relates to the people’s religious views, remains the same. Islam extensively shapes the culture, customs, traditions, lifestyle, and, most important, the centuries-long practice of self-government among the region’s residents. Today its significance is growing and this is having an impact on the forms and other aspects of the democratization process, as well as on the establishment and expansion of civil society institutions. This is being promoted, among other things, by the crease in nongovernmental noncommercial organizations, including religious charity associations. Not only is the cultural-historical mindset changing, but a new type of political thinking is also forming under the influence of the Islamic customs and morals passed down from generation to generation, which is making it possible to create the foundations of a civil society. The ways in which power is being transferred at present in Muslim countries, including in the Middle East, usually become a set pattern and can be improvised by the elites, including in he Central Asian states. The aim is to make a smooth transfer to more contemporary forms of government while retaining the traditional foundations and succession of power. So it seems expedient to examine this question using the example of the Middle Eastern Arab states since their sociopolitical relations are the closest to those currently practiced in Central Asia.